Kualitas Hijauan Rumput Gajah (Pennisetum purpureum) Berbeda Tipe Pertumbuhan: Review Kuantitatif: Quality of Napier Grass Forage (Pennisetum purpureum) with Different Growth Type: Quantitative Review - Eko Heru Dumadi; Luki Abdullah; Heri Sukria (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2021)
Study on the data of forage quality was conducted to determine the quality of napier grass forage with different growth and morfological type. In Indonesia, there are two types of napier grass, namely the tall and short type. The data used in this study were of proximate and van soest analysis of tall-type napier grass forage Pennisetum purpureum Schum and short-type napier grass, cultivar Mott dwarf, which were obtained from the Bekasi Feed Quality and Certification Center and data obtained from journals. The results of the study showed that dry matter content of short-type napier grass was higher than those of tall-type napier grass (23% vs 20%), while fiber fractions such as crude fiber, NDF and ADF of short-type napier grass were lower than those of tall-type napier grass 32% vs 29%, 70% vs 65%, 43% vs 39%, respectively. It is therefore relative forage quality (RFQ) of short-type napier grass was higher than those of tall-type napier grass (68 vs 57). It is concluded that related to dry matter and fiber fraction value, the quality of short-type napier grass (cv. Mott) is better than those of tall-type napier grass. Key words: cultivar Mott, Pennisetum purpureum, relative forage quality (RFQ), short-type napier grass, tall-type napier grass